Makna Sirih Pinang Dalam Upacara Penerimaan Tamu Dan Penobatan Kepala Suku Atau Kepala Soa Di Desa Wagrahi Kecamatan Fena Leisela Kabupaten Buru Provinsi Maluku : Kajian Pendidikan Hindu - Waemese, Ita; Widiastithi, Ni Nyoman Sugi; Rai, I Gusti Ngurah (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2023)
This research will discuss the meaning of betel nut as a very important symbol used in the reception ceremony and the coronation ceremony of the head of the tribe/soa, the researcher examines the elements contained in betel, areca nut and lime. The purpose of this study is to use qualitative methods with descriptive analysis through interviews, observation and documentation studies, then the theory used is the theory of symbols and religion. The findings from the results of this study, the authors know the meaning of betel nut in the reception ceremony and the coronation ceremony of the tribal chief. Where lime is a symbol of human bones, betel is a symbol of human veins and areca nut is a symbol of human flesh. All three contain a very strong meaning in human beings.